Konsep Pendidikan Anak Menurut M. Quraish Shihab dalam Perspektif Pendidikan Islam - Zulfa, Indana; Tajib, Ach. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study explores the concept of child education according to M. Quraish Shihab within the framework of Islamic education. Education is a fundamental element in human development, and in Islamic thought, it is not merely a process of transferring knowledge, but a holistic effort to nurture innate human potential in accordance with divine guidance. M. Quraish Shihab, a renowned Indonesian Qur’anic exegete and scholar, offers a rich educational perspective grounded in the Qur’an, combining classical Islamic tradition with contemporary educational insights. Employing a philosophical approach and library research methodology, this study analyzes primary sources Shihab's major works and supports them with relevant secondary literature. The findings indicate that Shihab’s concept of child education is centered around three essential components: aqidah (faith), ibadah (worship), and akhlaq (morality). These components are interrelated and rooted in the child’s natural disposition (fitrah), which must be nurtured through love, compassion, and example rather than coercion. Education should begin early, even from the womb, and be modeled by parents and teachers as role models. Shihab’s educational thought aligns deeply with the Qur’anic view of human development, emphasizing the formation of a balanced, faithful, and morally upright individual. His ideas remain highly relevant for addressing contemporary educational challenges in Muslim societies.